2010
DOI: 10.4028/www.scientific.net/amr.152-153.1788
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Antioxidant Activity of Collagen from the Chinese Soft-Shelled Turtle (<i>Pelodiscus sinensis</i>)

Abstract: Collagen is regarded as one of the most useful biomaterials. Collagen was extracted from wild Chinese soft-shelled turtles (Pelodiscus sinensis) and its molucular patterns and antioxidant activities were investigated. The SDS-PAGE analysis revealed that the collagen had three α bands with an approximate molecular weight of 400-410 kDa, which was similar to type V collagen with a molecular pattern of α1(V)α2(V)α3(V) or α1(V)[α2(V)]2. The antioxidant activity of collagen were examined by the radical-scavenging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Lu et al (2010) obtained the collagen from calipash of P. sinensis by pepsin digestion and reported that the extracted collagen belonged to typical collagen I with two α and one β chains. Whereas Liu et al (2010) found that the collagen type of P. sinensis belongs to collagen V with an approximate molecular weight of 400-410 kDa, we did not find high expression of collagen V. Further research remains to be done to explain the absence of collagen V.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Lu et al (2010) obtained the collagen from calipash of P. sinensis by pepsin digestion and reported that the extracted collagen belonged to typical collagen I with two α and one β chains. Whereas Liu et al (2010) found that the collagen type of P. sinensis belongs to collagen V with an approximate molecular weight of 400-410 kDa, we did not find high expression of collagen V. Further research remains to be done to explain the absence of collagen V.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies on P. sinensis have mainly focused on the nutritional value, such as preparation and characterization of collagen for biomaterial applications (Nobuhiro et al, 2009;Liu et al, 2010;Lu et al, 2010). The molecular mechanisms behind collagen formation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are almost 30 collagen types, among them type I collagen is a major structural protein found in large quantities in various parts of the body, especially in the skin, bones and tendons (Mimura et al, 2006), which accounts for most of the collagen mass in non-cartilaginous tissues. In our previous studies as well as other researchers' work, it was found that collagen is abundant in the calipash of P. sinensis and has been found to be the dominant type of collagen in normal turtle calipash (Liu et al, 2011;Nagai et al, 2009;Yang et al, 2016). Collagen is therefore given significant attention in terms of functioning as the support of calipash maintenance that relates to the unique characteristic of turtle calipash (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 81%